Maternal immunity of native cattle breed vaccinated with attenuated MP-12 rift valley fever vaccine - Ibrahim, A. M.; Said, T. A.; Shalkamy, Eman M.; Mohammed, G. K.; Azab, H. A. M. (2011)
The present study aimed to evaluate the immunity and abortagenicity and teratogenicity effect in vaccinated pregnant native cattle breed with 5 log 10 TCID50/ animal live mutagenized RVF MP-12 vaccine. The maternal immunity in its delivered calves was investigated by using serum neutralization test (SNT) and Enzyme Linked Immunosorbent Assay (EUSA). There was no body temperature elevation or any other RVF clinical signs, especially abortion or tratogenic changes in cows and their delivered calves neither after vaccination nor after parturition. The live attenuated MP-12 vaccine was also effective to induce immunity at protective level within 14 days till parturition. The immunity was detected early in all groups of delivered calves from 1st day till 2 months in group 1 (G1), 3 months in (G2) and (G3). The colostrum had antibodies for the first 3 days post-parturition. The vaccination of pregnant cattle at 2- 5 months of pregnancy was recommended.
Includes references.
Summary in Arabic.
1
Keywords: Cattle -- Diseases -- Egypt; Cattle -- Vaccines; Cattle -- Virus diseases -- Control; Rift valley fever -- Egypt